Bentonite-based sodium alginate/ dextrin cross-linked poly (acrylic acid) hydrogel nanohybrids for facile removal of paraquat herbicide from aqueous solutions. (March 2022) - Thakur, Sourbh; Verma, Ankit; Raizada, Pankaj; Gunduz, Oguzhan; Janas, Dawid; Alsanie, Walaa F.; Scarpa, Fabrizio; Thakur, Vijay Kumar
Abstract: Removal of hazardous herbicides from the aqueous solution is critical for overcoming health-related issues across the wider population. In the current work, we have prepared sodium alginate (SAlg), dextrin, and acrylic acid (AA) based cross-linked hydrogels, composed of bentonite incorporated in the biocompatible hydrogel matrix. This hydrogel composite can remove highly toxic herbicide paraquat (PQ). As-synthesised hydrogel (SAlg/dextrin-cl-PAA) and hydrogel composite (SAlg/dextrin-cl-PAA/bentonite) were further analysed by infra-red spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and thermogravimetric analysis (TGA/DSC). For the first time, PQ adsorption onto sodium and dextrin-based hydrogel was also evaluated. The measured highest removal capacities were 76.923 and 90.909 mg g −1 for the SAlg/dextrin-cl-PAA and SAlg/dextrin-cl-PAA/bentonite, respectively. Pseudo-second-order (PSO) and Langmuir isotherm models have shown to be best suited for accurately describing the adsorption mechanism. A thermodynamics study verified that the adsorption of PQ on adsorbents is spontaneous, favourable and exothermic. Moreover, reusability analysis shows that the adsorbents possess good reproducibility even after six successive cycles. The adsorption results demonstrate that the synthesised adsorbents are very efficient for removing herbicides (PQ) from wastewater. Graphical abstract: Image 1 Highlights: Paraquat herbicide accumulation in environment is an emerging problem across the world. Sodium alginate (SAlg), dextrin and acrylic acid (PAA) based biopolymeric hydrogel network was successfully designed. Bentonite was incorporated in SAlg/dextrin-cl-PAA matrix to produce SAlg/dextrin-cl-PAA/bentonite. SAlg/dextrin-cl-PAA/bentonite showed high adsorption of paraquat herbicide. SAlg/dextrin-cl-PAA/bentonite can be reused effectively for up to six paraquat adsorption-desorption cycles.